Surveying the scope, success, and challenges of plant conservation community science - Finch, Jessamine; Jasny, Micah; Kucera, Katherine F.; Kiefer, Gretel (Frontiers in Conservation Science, 2022)
First emerging at the end of the 20th century, community science (a.k.a. citizen science), utilizing volunteers and volunteer-contributed data, has become a major component of biological conservation worldwide. Interacting factors including limited funding, technology availability, and public interest present a unique opportunity for conservation scientists and practitioners to benefit from larger datasets with broader spatial and temporal reach than possible from professional researchers alone. In tandem with benefits to science, volunteers gain hands-on research experience, scientific knowledge, outdoor opportunities, and community. However, this approach is far from universally adopted, as some researchers question the accuracy and value of community science data and entrusting volunteers with sensitive data, such as rare plant locations. We conducted a global assessment of community science projects that conduct rare plant monitoring to evaluate the value of community science in plant conservation. We identified projects through research and targeted outreach. Through digital surveys of project managers and project volunteers, we collected qualitative and quantitative data addressing the efficacy of projects in regard to a number of predictor variables (e.g. staffing, funding, program size, data management, volunteer training, and demographics) and metrics of success (e.g. number of volunteers engaged, monitoring surveys assigned and completed, and publications). We report the qualities of successful plant conservation community science projects to encourage the establishment of new projects, the improvement of existing ones, and maximum application of volunteer-contributed rare plant monitoring datasets. We propose the establishment of a community science rare plant monitoring network to facilitate sharing ideas, strategies, and tools for project success.